A Qualitative Exploration of COVID+ Learning Network Webinars: Healthcare Learnings at Pace in a State of Rapid Change - Brett Morris; Jo-Anne Rayner; Chantelle Bartlett; Deirdre Fetherstonhaugh; Emmalee McArdle; Amber O'Brien (SAGE Publishing, 2024)
Background: Learning Networks are increasingly used to educate clinicians and disseminate information to health professionals. During the height of the second COVID-19 lockdown in Victoria, Australia, COVID+ Learning Network webinars were introduced as a mechanism for disseminating emerging evidence and up-to-date information to health service managers, and primary care and community healthcare clinicians, and for obtaining feedback from the healthcare sector. Methods: A qualitative descriptive study design was used to explore the COVID+ Learning Network webinars from users' perspectives. Fifteen webinar participants from different professional backgrounds, roles during the COVID-19 pandemic, and geographic locations were individually interviewed. Results: The webinars attracted state-wide engagement and participants described them as an effective way to inform and support health services, and primary care and community healthcare clinicians. However, data analysis revealed important considerations for using Learning Networks to disseminate information in the future. In particular, the importance of tailoring the webinars to address the specific needs of the different participant groups was highlighted. Conclusion: Health service managers, and primary care and community healthcare clinicians, require information pertinent to their specific roles, with consideration of geographic and socio-economic factors important to planning webinar content. Future learning network webinars would benefit from a more targeted approach to address the specific informational needs of the groups participating.